Parents' Responsibilities Towards Children in the Era of Society 5.0 ‎in the Perspective of Islamic Family Law in Indonesia - Arvyan, Ariq; Cahyadi, Teguh Dwi (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze parental responsibility towards children in the Society 5.0 era from the perspective of Islamic family law in Indonesia, as well as to identify relevant parenting patterns and challenges faced in Jakarta. The Society 5.0 era presents new challenges for Muslim families, especially related to digital interactions, the influence of technology on children's morals, and Sharia responsibilities that must still be carried out by parents. The research method used is a descriptive qualitative approach with documentation techniques and interviews with several informants (parents, religious educators, and Islamic family law experts). The results of the study show that: a) Parental responsibility based on maqāṣid sharia now extends to the digital realm, including maintaining the honor and security of children's data. b) Parenting patterns such as smart-parenting, techno-modeling, and digital family contracts can strengthen children's spiritual and moral interactions in cyberspace. c) The main obstacles include time constraints, digital literacy gaps, children's dependence on gadgets, and minimal systemic support. d) The solutions offered include Islamic parenting training, selection of sharia applications, weekly reflections with children, and strengthening communities based on Islamic values.